Catalytic cracking of CH3Cl on copper-based phases. Issue 6 (17th February 2022) - Blaser, Eugénie; Rosier, Cécile; Huet, Michel; Geantet, Christophe; Loridant, Stéphane
Abstract : CuCl and Cu are active phases for CH3 Cl cracking, a side reaction of the methylchlorosilanes direct synthesis. In the presence of black carbon simulating coke, CuCl is reduced leading to Cu, inactive for the direct synthesis, and chlorinated coke. Abstract : The methylchlorosilanes synthesis from Si and CH3 Cl, also called the direct synthesis suffers from a side-reaction during which the CH3 Cl reactant cracks and forms carbonaceous compounds, called coke. It leads to deactivation of the Cu3 Si active phase formed by reaction of Si and a Cu precursor. This paper deals with the CH3 Cl cracking on the copper-based phases CuCl and Cu, without and with Si (during the direct synthesis). In the former case, the two phases were supported either on carbon black or on silica. Both CuCl and Cu were shown to be active phases with similar reaction rate and the stoichiometry of the CH3 Cl cracking was determined from the selectivity values. Cu turns into CuCl by reacting with CH3 Cl. CuCl is stable on SiO2 while it is reduced on carbon black support which is chlorinated during the cracking. This key result reveals an original effect of coke since it favours formation of metallic Cu inactive for the direct synthesis in addition to covering the active sites leading to deactivation.